1994
DOI: 10.1097/00007890-199410000-00005
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Randomized Trial Comparing Sequential Ganciclovir-High Dose Acyclovir to High Dose Acyclovir for Prevention of Cytomegalovirus Disease in Adult Liver Transplant Recipients

Abstract: Cytomegalovirus disease is an important cause of morbidity following liver transplantation. To date there has not been an effective prophylaxis for CMV disease after liver transplantation. One hundred fortythree patients were randomized to receive either high dose oral acyclovir (800 mg 4 times a day) alone for a months after transplantation Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 9 publications
(10 reference statements)
2
18
0
Order By: Relevance
“…all but D-/R-) and D+/R-heart and liver transplant recipients. [91][92][93] In some scenarios, data are contradictory as to what the appropriate duration of intravenous therapy should be. For example, while some studies have suggested that short course therapy is not adequate for high risk liver transplant recipients, [60] use of 14 days of intravenous ganciclovir prophylaxis resulted in good outcomes in pediatric liver transplant recipients.…”
Section: Valaciclovirmentioning
confidence: 99%
“…all but D-/R-) and D+/R-heart and liver transplant recipients. [91][92][93] In some scenarios, data are contradictory as to what the appropriate duration of intravenous therapy should be. For example, while some studies have suggested that short course therapy is not adequate for high risk liver transplant recipients, [60] use of 14 days of intravenous ganciclovir prophylaxis resulted in good outcomes in pediatric liver transplant recipients.…”
Section: Valaciclovirmentioning
confidence: 99%
“…Most trials conducted on liver transplant recipients have not shown a benefit of acyclovir prophylaxis ( 28, 29). Two trials did show benefit in seropositive recipients ( 30, 31), who were given intravenous acyclovir for 10 days, followed by high‐dose oral acyclovir for the first 3 months after transplantation ( 30), or 2 g/day of oral acyclovir for 4 months after transplantation ( 31).…”
Section: Selected Trials Of Prophylaxis In Solid Organ Transplantationmentioning
confidence: 99%
“…A randomized trial in Pittsburgh compared two prophylactic regimens, high‐dose oral acyclovir for 3 months versus intravenous ganciclovir for 2 weeks, followed by high‐dose oral acyclovir for 3 months ( 28). There was a decreased incidence of disease in seropositive patients, but not in high‐risk recipients, although some decreased disease severity was observed ( 28). The incidence of disease in high‐risk individuals in the ganciclovir and acyclovir groups was 50% and 65%, respectively.…”
Section: Selected Trials Of Prophylaxis In Solid Organ Transplantationmentioning
confidence: 99%
“…The first entails administration of an antiviral agent to all transplant recipients immediately after transplantation (i.e., universal prophylaxis). Among 143 patients randomized either to intravenous ganciclovir for 2 weeks followed by high‐dose acyclovir for 10 weeks or to 12 weeks of high‐dose acyclovir alone,12 the incidence of CMV disease was lower in the ganciclovir‐acyclovir group (9% vs. 28%). However, the effect in the subgroup of high‐risk patients (D+/R−) was less pronounced (43% vs. 64%).…”
Section: Viral Infectionsmentioning
confidence: 99%